2022
DOI: 10.1111/acer.14893
|View full text |Cite
|
Sign up to set email alerts
|

Mice lacking α4 nicotinic acetylcholine receptors are protected against alcohol‐associated liver injury

Abstract: Background: Chronic heavy alcohol consumption is a major risk factor for the development of liver steatosis, fibrosis, and cirrhosis, but the mechanisms by which alcohol causes liver damage remain incompletely elucidated. This group has reported that α4 nicotinic acetylcholine receptors (α4 nAChRs) act as sensors for alcohol in lung cells.This study tested the hypothesis that α4 nAChRs mediate the effects of alcohol in the liver.Methods: Expression of acetylcholine receptor subunits in mouse liver was determin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 59 publications
0
2
0
Order By: Relevance
“…Watson et al reported that α4nAChR was the most abundantly expressed subtype of nicotinic receptor in mouse liver [20]. In this study using knockout (α4 KO) mice, the processes of alcohol-induced liver damage were either absent or significantly reduced in α4 KO animals [20]. Therefore, these results show that the α4nAChR subunit has a major role in liver damage.…”
Section: Introductionmentioning
confidence: 47%
See 1 more Smart Citation
“…Watson et al reported that α4nAChR was the most abundantly expressed subtype of nicotinic receptor in mouse liver [20]. In this study using knockout (α4 KO) mice, the processes of alcohol-induced liver damage were either absent or significantly reduced in α4 KO animals [20]. Therefore, these results show that the α4nAChR subunit has a major role in liver damage.…”
Section: Introductionmentioning
confidence: 47%
“…Various subtypes of nicotinic receptors may play a role in the processes of liver injury [17][18][19]. Watson et al reported that α4nAChR was the most abundantly expressed subtype of nicotinic receptor in mouse liver [20]. In this study using knockout (α4 KO) mice, the processes of alcohol-induced liver damage were either absent or significantly reduced in α4 KO animals [20].…”
Section: Introductionmentioning
confidence: 61%